Vasoactive Intestinal Peptide-Secreting Tumor - Femmy Nurul Akbar; Dadang Makmun (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2009)
Vasoactive intestinal peptide-secreting tumor (VIPoma) is one of the tumors which cause “ watery diarrhea, hypokalemia, hypochlorhydria and acidosis syndrome” (WDHHA syndrome). These tumor caused by to non-insulin-secreting pancreatic islet tumor that associated with elevated vasoactive intestinal polypeptide (VIP) plasma level. VIP is a potent stimulator of gut cyclic adenosine monophosphate (cAMP) production, which leads to massive secretion of water and electrolytes mainly potassium. Over expression of VIP causes diarrhea and cancerous growth. The other clinical features of VIPomas such as hypercalcemia, abdominal discomfort, tetany, facial flushing are associated with the actions of VIP, which stimulate intestinal secretion, inhibit gastric acid secretion. VIP also regulates the synthesis, secretion, and action of neuroendocrine hormones such as secretin, glucagon, prostaglandin E, somatostatin and pentagastrin as well as cytokines and chemokines. Diagnosis is based on clinical, laboratory test show elevation VIP level, electrolyte and acid base imbalance also imaging such as CT scan or magnetic resonance imaging (MRI) which shows primary tumor in the pancreas and metastasis especially in the liver. Somatostatin receptor scintigraphy may be useful in identifying extrapancreatic VIPomas, i.e. the sympathetic chain, colon, bronchus and occult or distant metastases. Initial treatment is to correct volume, electrolyte, and acid-base abnormalities with intravenous normal saline, potassium chloride, and, sodium bicarbonate. Somatostatin or long acting ocreotide is effective in reducing serum VIP levels and promptly controlling diarrhea. Interferon alpha and glucocorticoid may be useful for reducing symptoms. Surgical resection depends on staging of pancreatic tumor.   Keywords: VIPoma, WDHHA syndrome, VIP, non insulin secreting pancreatic islet tumor